The Dendrothripinae (Thysanoptera, Thripidae) of Saudi Arabia, with new records, one new species, and revised status of Pseudodendrothrips stuardoi (Moulton) - Rasool, Iftekhar; Mound, Laurence A.; Soliman, Ahmed M.; Aldhafer, Hathal M. (Zootaxa, 2021)
Two genera Dendrothrips Uzel and Pseudodendrothrips Schmutz are recorded from Saudi Arabia. A key is provided to eight members of Dendrothrips that have antennae with 9-segments and D. saudicus sp. n. is described in this group. P. aegyptiacus (Priesner) and P. stuardoi are newly reported from Saudi Arabia, with P. stuardoi rev. stat. from the leaves of Ficus carica being newly distinguished from P. mori (Niwa) that lives on the leaves of Morus alba. Some published records of P. mori from Mediterranean countries are possibly misidentifications of P. stuardoi.